Cateterismo Uretral: un tema para la reflexión (2005)
ABSTRACT: This article deals with urethral catheterism and it is inspired by the actions for the preventive and integral care of the persons. A technical guide for the procedure is proposed with contributions of others evidence based guides. The analysis of the implicated risks is taken into account, particularly those related to urinary infection which is an important cause of interhospitalary infection. Accordingly the problems related with the role and the nurses professional responsibility in this procedure are considered stressing how has to be practiced in the utmost conscious manner, with the deepest knowledge of the instructions, risks, handling and alternative procedures helping urinary elimination. The beneficial ethical principles are stressed to warrant the quality of the nursing care to ensure the patient and his family integral well-being.